2006
DOI: 10.1016/j.jmb.2006.06.055
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Core Structure of Lysozyme Amyloid Fibrils by Proteolysis

Abstract: Human lysozyme variants form amyloid fibrils in individuals suffering from a familial non-neuropathic systemic amyloidosis. In vitro, wild-type human and hen lysozyme, and the amyloidogenic mutants can be induced to form amyloid fibrils when incubated under appropriate conditions. In this study, fibrils of wild-type human lysozyme formed at low pH have been analyzed by a combination of limited proteolysis and Fouriertransform infrared (FTIR) spectroscopy, in order to map conformational features of the 130 resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
117
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

5
4

Authors

Journals

citations
Cited by 143 publications
(127 citation statements)
references
References 91 publications
9
117
0
1
Order By: Relevance
“…Proteolytic Mapping of the Core Region of the OVA FibrilThe role of the hB region in the heat-induced fibril formation of OVA was further assessed by limited proteolysis, which has been exploited successfully to analyze aspects of fibril formation (55). Proteolytic cleavage generally occurs at flexible regions of a polypeptide chain, and the structured regions of the amyloid fibril correspond to the most highly protease-resistant region.…”
Section: Mvlvmentioning
confidence: 99%
“…Proteolytic Mapping of the Core Region of the OVA FibrilThe role of the hB region in the heat-induced fibril formation of OVA was further assessed by limited proteolysis, which has been exploited successfully to analyze aspects of fibril formation (55). Proteolytic cleavage generally occurs at flexible regions of a polypeptide chain, and the structured regions of the amyloid fibril correspond to the most highly protease-resistant region.…”
Section: Mvlvmentioning
confidence: 99%
“…In a previous study, it was shown by a combined approach of limited proteolysis and Fourier transform infrared spectroscopy (FTIR) that the core region of mature fibrils from human lysozyme produced in vitro at low pH is primarily formed by residues 32-108 in the 130-polypeptide chain of the protein and that the rest of the chain is relatively unstructured. 14 The segment 32-108 corresponds to the region found to undergo cooperative local unfolding in the amyloidogenic variants I56T and D67H of human lysozyme 15,16 and to be amyloidogenic in the homologous hen lysozyme. 17,18 Given the high stability of wild-type human lysozyme, [19][20][21] conditions such as low pH and high temperature or ethanol have been previously used to populate a partially unfolded state that is prone to form fibrils.…”
Section: Introductionmentioning
confidence: 99%
“…Protein aggregation occurs in many diseases (7)(8)(9). The best mechanistically characterized examples involve the polymerization of aggregationprone peptides (10,11) or small proteins to give well-defined fibrils based on a regular repeat structure (12)(13)(14)(15)(16)(17)(18). The fibrillar aggregates have a characteristic cross-β X-ray diffraction pattern and bind such dyes as Congo Red and Thioflavine T (ThT) (16).…”
mentioning
confidence: 99%